2018
DOI: 10.1002/jez.2156
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of the transcription factors‐sal‐like 1 and spalt‐like transcription factor 3 on egg production‐related traits in Chinese Dagu hens

Abstract: Transcription factors (TFs) encoded by SALL1 and SALL3 genes play central roles in the regulation of ovarian development in hens. The present study aimed to examine polymorphisms of these two genes in Chinese Dagu chickens, and to identify the effects of TFs on the laying performance. Among the population, two novel single-nucleotide polymorphisms (SNPs) were identified by single-strand conformation polymorphism (SSCP) in the amplicons of the candidate genes. The effect of the SNP (729C > A) in exon 2 of SALL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The chicken is large and solid, with strong foraging ability, quality and quantity eggs, thick and solid eggshell, fresh and tender meat, and strong disease resistance. Our study had confirmed the correlation between csal1 and laying traits of Chinese Dagu chicken ( Zhu et al., 2018 ). However, the commercial production of Chinese Dagu chicken lacks systematic research on their laying performance.…”
Section: Introductionsupporting
confidence: 81%
“…The chicken is large and solid, with strong foraging ability, quality and quantity eggs, thick and solid eggshell, fresh and tender meat, and strong disease resistance. Our study had confirmed the correlation between csal1 and laying traits of Chinese Dagu chicken ( Zhu et al., 2018 ). However, the commercial production of Chinese Dagu chicken lacks systematic research on their laying performance.…”
Section: Introductionsupporting
confidence: 81%
“…PCR-SSCP has been used for several traits of animals such as wool characteristics [23], milk production traits [24], profile of sheep fatty acids [25], detection of Escherichia coli in the black swan [26], growth and carcass traits in lambs [27], reproductive traits in cattle [28], egg production traits in hens [29], body weight traits on chicken [30][31][32], gene study for fat-tailed and nonfat-tailed sheep [33], serotyping dichelobacter nodosus [34], mitochondrial diversity role in the productivity of quails [35], miR-9 gene affects litter size in goats [36], mutations in porcine [37], prolactin gene and association with egg production in ducks [38], wool fibre diameter in ewes [39], lactoferrin gene affects milk content in buffaloes [40], milk traits in yaks [41], association between MyoG gene and egg quality [42].…”
Section: Animalsmentioning
confidence: 99%
“…57 However, PCR-SSCP was considered as a cornerstone in recent post-PCR genotyping studies on poultry, such as egg-production traits, body weight characteristics, and intramuscular fat content. [58][59][60] Because of its powerful ability to identify unknown SNP(s), Table 1. The Main Differences Between PCR-RFLP and PCR-SSCP Methods…”
Section: Applicationsmentioning
confidence: 99%
“…[62][63][64] With respect to fish and amphibians, species identification and the detection of environmental samples and closely related organisms were recently conducted using PCR-RFLP. [56][57][58][59][60][61][62][63][64][65][66][67][68] The PCR-SSCP was used in the detection of parasite species. 69 The ease of the use of PCR-RFLP was demonstrated in its successful implementation in species identification and discrimination in algae, bacteria, and fungi.…”
Section: Parameter Of Comparison Pcr-rflp Pcr-sscpmentioning
confidence: 99%